Primitive reflexes in Parkinson's disease. - Vreeling, F W (1993)
A standardised protocol for the examination of 15 primitive reflexes in which the amplitude and the persistence were scored separately, was applied to 25 patients with Parkinson's disease and an equal number of healthy matched control subjects. Most reflexes were found considerably more often in the patients than in the control subjects, especially the snout, the glabellar tap, and its variant, the nasopalpebral reflex. Only the mouth open finger spread reflex was present more often in the control subjects. For all reflexes except this last, the scores for amplitude and persistence of the reflexes for the control group never exceeded the scores for the patient group. Reflexes persisted more often in the patients than in the control subjects. Parkinsonism alone can explain a large number of primitive reflexes, irrespective of the severity or duration of the disease. In contrast, the number of reflexes was related more closely to cognitive scales. It is concluded that such reflexes may be helpful in diagnosing Parkinson's disease. In addition, a standardised protocol for eliciting and scoring is essential for the study of these reflexes in parkinsonism and other neuropsychiatric conditions.